Research as a tool for empowerment : theory informing practice - Schwarzer, David; Bloom, Melanie; Shono, Sarah (Research in second language learning., 2006)
Research as a Tool for Empowerment: Theory Informing Practice is an edited volume that includes an array of research-based chapters that not only further the field of second/foreign language research, but also provide practical implications to language classrooms in international and national settings. Chapters in this volume present a bridge between methodologically sound second/foreign language research and strong pedagogical implications. This volume includes the voices of researchers, graduate students, teachers, parents, and learners exploring the second/foreign language phenomena. The multiple voices of the contributing authors reflect the diverse readership of the Research in Second Language Learning series. Unlike previous anthologies in second/foreign language research, this volume presents studies from various research paradigms. Chapters include examples of various research methods from both quantitative and qualitative paradigms. Few previous anthologies have presented research based in multiple paradigms and from multiple perspectives. Research as a Tool for Empowerment: Theory Informing Practice not only presents these various perspectives, but it also makes the link from research to classroom implications and applications. The volume is unique as it makes a connection between different types of research and research methods and empowerment and issues of empowerment.